An Improved Turn Structure for Inducing β‐Hairpin Formation in Peptides. Issue 42 (12th September 2021) - Li, Xingyue; Sabol, Andrew L.; Wierzbicki, Michał; Salveson, Patrick J.; Nowick, James S.
Abstract: Although β‐hairpins are widespread in proteins, there is no tool to coax any small peptide to adopt a β‐hairpin conformation, regardless of sequence. Here, we report that δ‐linked γ( R )‐methyl‐ornithine ( δ MeOrn) provides an improved β‐turn template for inducing a β‐hairpin conformation in peptides. We developed a synthesis of protected δ MeOrn as a building block suitable for use in Fmoc‐based solid‐phase peptide synthesis. The synthesis begins with l ‐leucine and affords gram quantities of the N α ‐Boc‐ N δ ‐Fmoc‐γ( R )‐methyl‐ornithine building block. X‐ray crystallography confirms that the δ MeOrn turn unit adopts a folded structure in a macrocyclic β‐hairpin peptide. CD and NMR spectroscopy allow comparison of the δ MeOrn turn template to the δ‐linked ornithine ( δ Orn) turn template that we previously introduced and to the popular d ‐Pro‐Gly turn template. These studies show that the folding of the δ MeOrn turn template is substantially better than that of δ Orn and is comparable to d ‐Pro‐Gly. Abstract : δ‐Linked γ( R )‐methyl‐ornithine ( δ MeOrn) provides an improved β‐turn template for inducing a β‐hairpin conformation in peptides.